2017
DOI: 10.2967/jnumed.117.190850
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic PET Imaging of Mammary Microcalcifications Using 64Cu-DOTA-Alendronate in a Rat Model of Breast Cancer

Abstract: The development of improved breast cancer screening methods is hindered by a lack of cancer-specific imaging agents and effective smallanimal models to test them. The purpose of this study was to evaluate 64 Cu-DOTA-alendronate as a mammary microcalcification-targeting PET imaging agent, using an ideal rat model. Our long-term goal is to develop 64 Cu-DOTA-alendronate for the detection and noninvasive differentiation of malignant versus benign breast tumors with PET. Methods: DOTAalendronate was synthesized, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In addition, in these studies, it was shown that microcalcifications made of hydroxyapatite are actively produced by cancer osteoblast-like cells (OLCs) in a process similar to what occurs during physiological bone matrix formation [3840]. On the basis of this evidence, molecular imaging could be used to discriminate cancer from any other type of lesion by studying the metabolic activity of breast tissues associated with the presence of microcalcifications as shown by Ahrens et al in a mouse model [41].…”
Section: Diagnostic Imaging and Anatomic Pathology: An Alliance Fomentioning
confidence: 99%
“…In addition, in these studies, it was shown that microcalcifications made of hydroxyapatite are actively produced by cancer osteoblast-like cells (OLCs) in a process similar to what occurs during physiological bone matrix formation [3840]. On the basis of this evidence, molecular imaging could be used to discriminate cancer from any other type of lesion by studying the metabolic activity of breast tissues associated with the presence of microcalcifications as shown by Ahrens et al in a mouse model [41].…”
Section: Diagnostic Imaging and Anatomic Pathology: An Alliance Fomentioning
confidence: 99%
“…18 F is produced by cyclotrons, which are expensive and complex instruments but can produce [ 18 F]­NaF in large quantities without any further need for complicated radiosynthetic procedures . On the other hand, PET BPs rely on the use of radiometals and hence are bifunctional chelators that generally involve multistep syntheses and radiosynthetic procedures, which may require an automated synthesis module for clinical translation. , , The most promising radionuclide in the development of PET BPs is 68 Ga ( t 1/2 = 68 min; β + = 89%). This radiometal benefits from not only a short radiation decay half-life that minimizes radiation dose to patients but also availability from both cyclotrons and benchtop generators that can be installed in any radiopharmacy, allowing cyclotron-independent PET radiotracers on-site .…”
Section: Introductionmentioning
confidence: 99%
“…55−57 On the other hand, Fe 3 O 4 NPs have been demonstrated to promote OB proliferation and differentiation because of their innate magnetic properties. 58,59 However, previous research has shown that unconjugated AL is rapidly cleared from the blood (95% in 6 h), 60,61 and monodisperse Fe 3 O 4 NPs are easily uptaken by the reticuloendothelial system, 62 which reduces their therapeutic efficacy. In the current study, loading of AL and Fe 3 O 4 onto HA crystals prevented short burst release of functional components into the defect site; hence, the long-term release of bioactive molecules and the sustained magnetic stimulation by MNPs accelerated healing of osseous defects in osteoporotic situation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…AL is a powerful antiresorptive agent that is widely used for the treatment of systemic metabolic bone diseases. Many studies have claimed that AL could inhibit bone resorption via suppression of OC formation and function; meanwhile, it may also improve OB activity and osseointegration between implants and the native bone. On the other hand, Fe 3 O 4 NPs have been demonstrated to promote OB proliferation and differentiation because of their innate magnetic properties. , However, previous research has shown that unconjugated AL is rapidly cleared from the blood (95% in 6 h), , and monodisperse Fe 3 O 4 NPs are easily uptaken by the reticuloendothelial system, which reduces their therapeutic efficacy. In the current study, loading of AL and Fe 3 O 4 onto HA crystals prevented short burst release of functional components into the defect site; hence, the long-term release of bioactive molecules and the sustained magnetic stimulation by MNPs accelerated healing of osseous defects in osteoporotic situation.…”
Section: Resultsmentioning
confidence: 99%